Kinematic factors associated with start performance in World-class male sprinters. (19th July 2021) - Walker, Josh; Bissas, Athanassios; Paradisis, Giorgos P.; Hanley, Brian; Tucker, Catherine B.; Jongerius, Nils; Thomas, Aaron; von Lieres und Wilkau, Hans C.; Brazil, Adam; Wood, Matthew A.; Merlino, Stéphane; Vazel, Pierre-Jean; et al.
Abstract: The aim was to investigate the kinematic factors associated with successful performance in the initial acceleration phase of a sprint in the best male athletes in the World at the 2018 World Indoor Athletics Championships. High speed video (150 Hz) was captured for eight sprinters in the men's 60 m final. Spatio-temporal and joint kinematic variables were calculated from the set position to the end of the first ground contact post-block exit (GC1). Normalised average horizontal external power (NAHEP) defined performance and was the dependent variable for a series of regression analyses. Clear relationships were found between GC1 NAHEP and 10-m time, 60-m time, change in velocity, acceleration and contact time in the first ground contact (r = –0.74, –0.64, 0.96, 0.91 and –0.56, respectively). Stepwise multiple linear regression of joint kinematic variables in the first ground contact revealed that trunk angle at take-off and thigh separation angle at take-off explained nearly 90% of variation in GC1 NAHEP (R 2 = 0.89). The athletes' projection at take-off with a forward leaning trunk and large thigh separation is characteristic therefore of excellent initial acceleration performance and this will be a good visual guide for technical coaching instruction. This was the first study of its kind to adopt such a research design in a World-class sample in a representative environment. Future studies that combine detailed kinematic and kinetic data capture and analysis in such a setting will add further insight to the findings of this investigation.